ANALISIS KEBUTUHAN TENAGA KERJA BERDASARKAN METODE WISN DI LOGISTIK FARMASI RSUD ARIFIN ACHMAD PROVINSI RIAU - Tiara Tri Agustini; Seftika Sari; Nanda Mulyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Human resource is one the success of indicator of an aeffective and efficient hospital. Human resource planning in pharmaceutical logistic need to bee considered because pharmaceutical logistic plays an important role in the management of pharmaceutical supplies which will affect quality hospital services. Workload Indicators Staffing Need (WISN) method is a method calculate workforce requirements based on a real workload undertaken by workfoce. This study aim to determine the need workforce based workload in the pharmaceutical logistic RSUD Arifin Achmad Provinsi Riau. This study is observational method that is descriptive using free guided interview technique. Sampling in this study was carried purposive sampling method. The sample in this study are head installation pharmacy and pharmacist in charge of logistic. Based on WISN analysis, human resource requirement in pharmaceutical logistic RSUD Arifin Achmad are 17. Pharmaceutical logistic had 14 staff, so that pharmaceutical logistic is still short of 3 staff with a WISN ratio 0,82 which means there was a lack of staff in pharmaceutical logistic.